Challenges of diagnosing and managing the adolescent with heavy menstrual bleeding. Issue 143 (July 2016) - Zia, Ayesha; Rajpurkar, Madhvi
Abstract: Unpredictable, prolonged or heavy menstrual bleeding (HMB) may be expected for many adolescents soon after menarche. A decade of clinical experience and research has now established firmly that bleeding disorders (BD) are common in adolescents with HMB. Despite these advances, many questions remain, and several aspects of the diagnosis and management of BDs in adolescents are not supported by rigorous clinical trials. In this overview, four major areas will be discussed. First, we will discuss the frequency of BDs in young women with HMB. Up to 20% of older females with HMB are thought to have an underlying BD. Estimates from retrospective studies in adolescents suggest a prevalence that varies anywhere from 10 to 62%. Prospective studies with uniform hemostatic evaluation are needed to answer this question definitively. Second, we will review existing tools that help screen and diagnose adolescents with HMB with an underlying BD. Although identification of an underlying BD in older women with HMB is relatively straight forward, uncertainties remain for adolescents. Heavy menstrual bleeding in this age group may have different pathophysiological underpinnings than those in older women and may often be disregarded as anovulatory. There is an urgent need to develop novel tools, and evaluate existing diagnostic strategies in adolescents. Third, we will discuss the optimal medical management of HMB in young adolescents. As direct evidence is largely lacking, these areas are also subject to extrapolation from older women. Lastly, an important area- prediction, and management of future bleeding in those adolescents who are diagnosed with a mild BD-will be discussed. Throughout, areas of controversy and opportunities for further research are highlighted. Highlights: Bleeding disorders are common, yet often overlooked in adolescents with heavy menstrual bleeding (HMB). A comprehensive approach to HMB in adolescents is paramount to accurately diagnose bleeding disorders. Gaps in our present understanding related to adolescents with HMB need to be urgently filled by multicenter collaborative studies.